(1) 2x-3y=5

(2) 3x-(2y-3)/5=4

Simplify (2)

(5)3x - (5)(2y-3)/5 = 4(5)

15x - 2y + 3 = 20

(3) 15x - 2y = 17

2x - 3y = 5 multiply by -2 to get -4x + 6y = -10 (4)

15x - 2y = 23 multiply by 3 to get 45x - 6y = 51 (5)

Now add (4) and (5) to get

41x = 41 and solving for x we get

x = 1

To find y we substitute x = 1 into (1) and solve for y

2(1)-3y=5

3y = 2 - 5

3y = -3

y = -1

Check the answers in the 2nd equation

3x-(2y-3)/5=4

3(1) - (2(-1)-3)/5 = 4

3 - (-5)/5 = 4

3 - (-1) = 4

4 = 4 Checks...

So our answer is (1, -1)

We have to solve by elimination the set of equations:

2x - 3y = 5 ...(1)

3x - (2y-3)/5 = 4 ...(2)

3*(1) - 2*(2)

=> 6x - 9y - 6x + 2*(2y-3)/5 = 15 - 8

=> -9y + (2/5)(2y - 3) = 7

=> -45y + 4y - 6 = 35

=> -41y = 41

=> y = -1

(2)

=> 15x - 2y + 3 = 20

=> 15x - 2y = 17 ...(3)

2*(1) - 3*(3)

=> 4x - 6y - 45x + 6y = 10 - 51

=> -41x = -41

=> x = 1

**The solution is x = 1 and y = -1**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now